Russian Federation Gender Assessment - World Bank (Washington, DC, 2015)
An egalitarian socialist legacy and relatively high and growing levels of income, particularly over the last decade, have translated into fairly equal gender outcomes in Russia along many dimensions. There are no significant differences in education levels between men and women, and in recent years more young women have completed post-secondary education than young men. Girls outperform boys in reading in standardized exams and do as well as them in math and science. At first glance, women do not seem to have difficulties in transitioning from school to work or remaining employed over the life cycle. And female labor force participation is significantly above the levels observed in other countries in Europe and Central Asia, as well as in the Organization for Economic Cooperation and Development, or OECD. This new assessment of gender equality issues in Russia seeks to gauge the progress in all the domains of outcomes during the last 10 years, and to further understand the main causes behind the persisting gender gaps identified in the country. This assessment builds on the analytical framework proposed by the World Development Report 2012: gender equality and development (World Bank 2012a) to provide a general overview of gender issues in Russia, and it builds on literature at the frontier in economics to go deeper in the two selected topics: adult mortality and gender gap in pay.